The life cycle of an enterprise: evolution of the management model from inception to rebirth ("Journal "U". Economy. Management. Finance.", 2025)
The study reveals the dynamics of the enterprise life cycle through the lens of management functions. It demonstrates how the integration of modern tools helps overcome crises and extend the organization’s sustainability
Keywords: enterprise life cycle; management functions (P A I T); transition crises; proactive management